2014
DOI: 10.4236/oje.2014.414076
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Selected Environmental Pollutants on the Ultrastructure of the Gills in <i>Pinctada radiata</i> from Coastal Zones, Egypt

Abstract: There has been an increasing interest in marine oysters (order: Petridae) in recent years because their numbers are declining in many parts of the world and also because they are used as monitors of pollution. The present study describes the microscopic structure of gills as viewed by light and electron microscopy in two locations selected in Alexandria coast, Eastern Harbor (E.H.) and El Asafra. The specimens in the E.H. represent the presence of extracellular mineralized granules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…Effects of environmental stressors on immunological function in P. imbricata have been elucidated by Kuchel, Raftos, and Nair (2010), which demonstrated as fluctuations in environmental conditions affect circulating haemocytes and their cytochemistry. Such results are confirmed and implemented by the present investigation, in agreement with the hypothesis that physiological responses to environmental stresses in the P. imbricata specie complex, especially at the haemocyte level, may be valuable tools in monitoring programs, eventually coupled with other proposed targets, as gill ultrastructure (Hamed et al, 2014). Such an option, which has been recently proposed for another Pteriomorphia, that is, the Mediterranean endemic Spondylus gaederopus L. 1758 (Fabrello et al, 2022), for Pinctada ssp.…”
Section: Discussionsupporting
confidence: 91%
“…Effects of environmental stressors on immunological function in P. imbricata have been elucidated by Kuchel, Raftos, and Nair (2010), which demonstrated as fluctuations in environmental conditions affect circulating haemocytes and their cytochemistry. Such results are confirmed and implemented by the present investigation, in agreement with the hypothesis that physiological responses to environmental stresses in the P. imbricata specie complex, especially at the haemocyte level, may be valuable tools in monitoring programs, eventually coupled with other proposed targets, as gill ultrastructure (Hamed et al, 2014). Such an option, which has been recently proposed for another Pteriomorphia, that is, the Mediterranean endemic Spondylus gaederopus L. 1758 (Fabrello et al, 2022), for Pinctada ssp.…”
Section: Discussionsupporting
confidence: 91%
“…Ultrastructure analysis performed at the Transmission Electron Microscopy Laboratory, Eijkman Institute for Molecular Biology (EIMB), Indonesia. Samples preparation for TEM analysis is carried out referring to the Hamed et al (2014) methods. Samples were fixed in 2.5% glutaraldehyde solution (pH 7.2, buffered 0.1 M phosphate buffer) for 2-4 h at 4 o C and rinsed in 0.1 M phosphate buffer and then post-fixed in 1% osmium tetroxide (OsO4) solution for 2 h at 4 o C. After fixation, the samples were washed with 0.1 M phosphate buffer 4 times for 2 h and dryed with ascending grades of ethanol.…”
Section: Ultrastructure Analysis In Gillsmentioning
confidence: 99%
“…Currently study have revealed that bivalve can retain and perhaps accumulate heavy metals in their soft tissues, included in gills (Hamed et al, 2014). The primary organs for metal accumulation are gills, which also have the highest amounts of pollution.…”
Section: Introductionmentioning
confidence: 99%
“…They can be used in detecting and monitoring the recent environment in terms of pollution, therefore mollusks (bivalves and gastropods) are the cornerstone of this study. In most recent researches, there are several contributions towards the geochemical analysis using invertebrate shells (Hamed et al, 2014). Near-shore human activities may result in marine organisms being exposed to high concentrations of metals (Esslemont, 2000;El-Sorogy, 2008;Oladoja et al, 2015).…”
Section: Introductionmentioning
confidence: 99%